Mewujudkan Pedagang Aman COVID-19 dengan 3M pada Pandemi COVID-19 Di Kota Bontang - Lies Permana; Helwena Helwena (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2021)
In October 2020, it was found that the largest number of clusters for the spread of COVID-19 were family clusters, namely 37 clusters in Bontang City, East Kalimantan. In addition, cases of COVID-19 were also found originating from traders in the night market. Judging from the COVID-19 cases, the risk from traders who have shophouses as well as their living quarters with other family members is very vulnerable to the spread of COVID-19. This community service aims to increase knowledge and raise awareness of merchants about the 3M movements. A service was carried out by providing 3M programs to prevent COVID-19, distributing cloth masks according to standards, distributing media posters, and providing hand wash facilities in the merchant area. The target of this service is ten traders who own shop houses. There is an effect of counseling on increasing the knowledge of 10 traders who have shop houses in the Berbas Night Market area. All masks are distributed to all respondents. There is a media feed back that is shared for increasing knowledge. The availability a washing hands fasilities. There are three programs implemented in community service to prevent COVID-19 in traders in the Berbas night market area.